Kepastian Hukum Pengaturan Ketidakmampuan Kehendak dalam Kesepakatan Jual Beli Real Estate (Analisis Yuridis Putusan Nomor: 54/PDT.G/2024/PN.TTE) - Rezki Yul Permatasari; Rusdin Alaudin; Siti Barora Sinay (SENTRI: Jurnal Riset Ilmiah, 2025)
This study examines the legal certainty of regulating defects of will in real estate sales agreements, focusing on fraud as stipulated under Article 1328 of the Indonesian Civil Code. The research is motivated by inconsistencies in judicial practice when resolving real estate disputes arising from pre-contractual fraud, particularly the overlap between breach of contract and tort. The purpose of this study is to analyze the juridical position of defects of will in contractual relationships and to assess the appropriateness of judicial reasoning in adjudicating such disputes. This study uses normative legal research with statutory, conceptual, and case approaches, drawing on the Indonesian Civil Code and Decision Number 54/PDT.G/2024/PN.TTE. The findings show that pre-contractual fraud occurred through unfulfilled promises of building quality not included in the contract, resulting in a defective and uninhabitable house and limiting the buyer’s ability to claim compensation. Juridically, this study concludes that defects of will caused by fraud constitute a breach of contract and should form the legal basis for contract annulment rather than tort liability, given the contractual nature of the relationship. The court’s reliance solely on tort is therefore a misapplication of law that undermines legal certainty. This study contributes to Indonesian contract law by clarifying the relationship between defects of will and breach of contract and offering practical guidance for resolving real estate disputes consistently.